Does the island area also need to insist on salt iodization to prevent iodine deficiency disorders? a cross-sectional survey in Hainan Province, China - Wu, Hongying; Meng, Shizhu; Sun, Dingwei; Hu, Yuting; Wu, Tingou; Wang, Xiaohuan; Wang, Xingren; Liu, Ying; Peng, Chuyan; He, Bin; Meng, Fangang (Frontiers in Endocrinology, 2025)
BackgroundTo investigate the epidemiology and related factors of iodine deficiency disorders (IDD) in Hainan Province, to know the iodine nutrition status and thyroid disease status of residents, and to explore whether salt iodization should be adopted to prevent and control IDD in island areas. To provide a basis for the effective implementation of scientific iodine supplement prevention and control strategy.MethodsAll 21 cities, counties (districts) in the province were investigated. Superficial soil, residential drinking water, common food, urine samples of children, adults and pregnant women, household salt samples, thyroid B-ultrasound of adults and pregnant women, adult blood samples were collected. Soil iodine, water iodine, food iodine, urine iodine, daily salt intake, salt iodine, thyroid volume, nodules and thyroid function were measured.ResultsThe median iodine content in soil was 4.37mg/kg, the median iodine content in drinking water was 6.0μg/L, the iodized salt coverage rate was 98.6%, and the consumption rate of qualified iodized salt was 97.9%. The median urinary iodine concentration (MUIC) in children and adults was 180.3μg/L and 151.6μg/L, respectively, which was the adequate level of iodine. The median urinary iodine in pregnant women was 144.6μg/L, which was slightly lower than the adequate level. The main source of iodine intake was salt iodine, which contributed 59.8% to total dietary iodine. Kelp, milk and seaweed, whose contribution rates were 8.2%, 7.3% and 6.6%, respectively. The total iodine contribution rate of other foods was 18.1%, among which the contribution rate of fish, shrimp and crabs was only 2.4%. The overall prevalence of thyroid diseases was 27.01%. The detection rates of subclinical hypothyroidism and subclinical hyperthyroidism in males were significantly higher than those in females, and the detection rates of thyroid nodules and goiter were significantly lower than those in females. The detection rates of thyroid nodules in central mountainous areas were significantly higher than those in eastern and western coastal areas.ConclusionsAt present, the iodine nutrition level in Hainan Province is generally in a suitable state, and the iodine intake of residents mainly comes from iodized salt. The strategy of salt iodization prevention and control of IDD should be adhered to in island area.